Analisis Yuridis Mengenai Pengaturan Tindak Pidana Euthanasia (Suntik Mati) menurut 344 KUHP di Indonesia - Tengku Novita Artika; Mahzaniar (Inovasi Pratama Internasional. Ltd, 2023)
Euthanasia is defined as the act of ending someone's life to stop their suffering. Euthanasia is regulated in Article 344 of the Criminal Code, which states that anyone who takes another person's life at that person's own request, which is clearly stated with sincerity, is threatened with a maximum prison sentence of 12 years. From the sound of this article it can be concluded that a person is not permitted to take another person's life, even if the reason is at the victim's own request. This indicates the law's respect for a person's life, regardless of the person's own interests. The problem in this research is to find out the regulations for Euthanasia in the Criminal Code in Indonesia, how doctors act towards Euthanasia requests, what factors influence the occurrence of Euthanasia in Indonesia. This research is a case with interviews through the District Court and the Head of Lubuk Pakam District Hospital. The results of this research are that the regulation of Euthanasia in the Indonesian Criminal Code violates Article 340 of the Criminal Code which states that anyone who intentionally and with premeditation takes the life of another person is threatened with premeditated murder, with the death penalty or imprisonment for life or for a period of time. certain, a maximum of 20 years (twenty years). The doctor's review of Euthanasia requests is in the form of pure euthanasia, passive euthanasia, indirect euthanasia and active euthanasia (mercy killing). All types of euthanasia can be carried out by patients, the patient's family or doctors. Factors that influence the occurrence of Euthanasia in Indonesia are humanitarian factors, economic factors, the patient's condition, medical personnel viewing the treatment process as ineffective and feelings of pity for the patient's suffering.